Synthesis of kinase inhibitors containing a pentafluorosulfanyl moiety - Sansook, S; Ocasio, CA; Day, IJ; Tizzard, GJ; Coles, SJ; Fedorov, O; Bennett, JM; Elkins, JM; Spencer, J (Royal Society of Chemistry, 2017)
A series of 3-methylidene-1H-indol-2(3H)-ones substituted with a 5- or 6-pentafluorosulfanyl group has been synthesized by a Knoevenagel condensation reaction of SF5-substituted oxindoles with a range of aldehydes. The resulting products were characterized by X-ray crystallography studies and were tested for biological activity versus a panel of cell lines and protein kinases. Some exhibited single digit nM activity.